2010
DOI: 10.1002/jbmr.34
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced differentiation of human embryonic stem cells to mesenchymal progenitors by inhibition of TGF-β/activin/nodal signaling using SB-431542

Abstract: Directing differentiation of human embryonic stem cells (hESCs) into specific cell types using an easy and reproducible protocol is a prerequisite for the clinical use of hESCs in regenerative-medicine procedures. Here, we report a protocol for directing the differentiation of hESCs into mesenchymal progenitor cells. We demonstrate that inhibition of transforming growth factor b (TGF-b)/activin/nodal signaling during embryoid body (EB) formation using SB-431542 (SB) in serum-free medium markedly upregulated pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 83 publications
3
100
0
5
Order By: Relevance
“…In mouse trophoblast stem cells, activin promotes the acquisition of a labyrinth cell fate (60). Interestingly, the occurrence of EMT upon passage of SB431542-treated hESCs has been reported but in dissimilar culture conditions (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…In mouse trophoblast stem cells, activin promotes the acquisition of a labyrinth cell fate (60). Interestingly, the occurrence of EMT upon passage of SB431542-treated hESCs has been reported but in dissimilar culture conditions (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…SB431542 treatment has previously been used to generate mesodermal progenitors from hESCs [10,14]. Sanchez et al [14], however, found that hESCs, but not iPSCs, underwent differentiation into CD90 ϩ CD73 ϩ MSCs after treatment with SB431542.…”
Section: Discussionmentioning
confidence: 99%
“…Mahmood et al treated hESCs with SB431542 during EB formation to upregulate paraxial mesodermal and myogenic markers and then derived MSC-like cells from EB outgrowth cultures [10]. Sanchez et al exposed hESCs to SB431542 for 28 days to induce differentiation into multipotent progenitors [14].…”
Section: Embryonic Stem Cells/induced Pluripotent Stem (Ips) Cellsmentioning
confidence: 99%
“…Successive outgrowth cultures of the MCP, in the presence of 10% fetal bovine serum (FBS), demonstrated a step-wise progression from a heterogeneous EB outgrowth cell population, through an MCP population, to a homogeneous population of mesenchymal progenitors that expressed CD markers characteristic of mesenchymal stem cells (MSCs): CD44 (100%), CD73 (98%), CD146 (96%), and CD166 (88%). Lastly these mesenchymal progenitors verified their ability to differentiate into osteoblasts in vitro and could form ectopic bone upon subcutaneous implantation with hydroxyl-apatite/tricalcium phosphate ceramic powder (HA/TCP) in immune deficient mice [27].…”
Section: In Vivo Assaysmentioning
confidence: 76%
“…Detailed cellular and molecular analysis revealed the differentiation of SB-treated hEBs into muscle progenitor cells (MPC) [27]. Successive outgrowth cultures of the MCP, in the presence of 10% fetal bovine serum (FBS), demonstrated a step-wise progression from a heterogeneous EB outgrowth cell population, through an MCP population, to a homogeneous population of mesenchymal progenitors that expressed CD markers characteristic of mesenchymal stem cells (MSCs): CD44 (100%), CD73 (98%), CD146 (96%), and CD166 (88%).…”
Section: In Vivo Assaysmentioning
confidence: 99%